2019
DOI: 10.1039/c9cp01609k
|View full text |Cite
|
Sign up to set email alerts
|

Biological relevance of charge transfer branching pathways in photolyases

Abstract: The travel of a positive charge along a branching pathway of tryptophan residues in the PhrA photolyase.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Electron transfer is at the center of many biological phenomena, such as respiration, 107 photosynthesis, 108 damage and repair of DNA, 109 and magnetic compass in birds, 110 but also in technological applications, including polymer light-emitting diodes, photovoltaic devices, and organic field-effect transistors. 111 An increasing interest in simulating electron transfer in metal and semiconductor surfaces and interfaces has emerged in the last few years, as they are crucial for molecular junctions, [112][113][114][115] dissociative chemisorption, [116][117][118][119] photocatalysis, solar cells, waste processing, and quantum confinement devices.…”
Section: Electron Transfermentioning
confidence: 99%
“…Electron transfer is at the center of many biological phenomena, such as respiration, 107 photosynthesis, 108 damage and repair of DNA, 109 and magnetic compass in birds, 110 but also in technological applications, including polymer light-emitting diodes, photovoltaic devices, and organic field-effect transistors. 111 An increasing interest in simulating electron transfer in metal and semiconductor surfaces and interfaces has emerged in the last few years, as they are crucial for molecular junctions, [112][113][114][115] dissociative chemisorption, [116][117][118][119] photocatalysis, solar cells, waste processing, and quantum confinement devices.…”
Section: Electron Transfermentioning
confidence: 99%
“…As for the features of the ET in that protein and perhaps in PCF in general, it was shown that it is the polarization of the solvent at the surface of the protein that makes the process exergonic and thus unidirectional. Holub et al (53) then investigated the interesting case of a class III cyclobutane pyrimidine dimer photolyase from Agrobacterium tumefaciens, which features not just one but two different, branching ET pathways containing a total of six Trp side chains, which were both found to play a role in the photoreduction of FAD. They discovered an intriguing thermodynamic and kinetic competition between the two pathways: One pathway supports a faster ET, while the other pathway stabilizes the final product better.…”
Section: Examples: Photolyases and Cryptochromesmentioning
confidence: 99%
“…Ths process allows them to provide atomic-level insight into the coupling of these processes. The example shown considers two different ET pathways in a photolyase protein PhrA(53). (a) The active site of PhrA, showing the amino acid side chain participating in the branching electron transfer pathways.…”
mentioning
confidence: 99%
“…Electron transfer is at the center of many biological and technological applications, such as respiration, 87 photosynthesis, 88 damage and repair of DNA, 89 and magnetic compass in birds, 90 but also polymer light-emitting diodes, photovoltaic devices, and organic field-effect transistors. 91 An increasing interest in simulating electron transfer in metal and semiconductor surfaces and interfaces has emerged in the last few years, as they are crucial for molecular junctions, [88][89][90][91] dissociative chemisorption, [92][93][94][95] photocatalysis, solar cells, waste processing, and quantum confinement devices. [96][97][98][99][100] Several perspectives on nonadiabatic dynamics and theoretical aspects of charge transport are available.…”
Section: Electron Transfermentioning
confidence: 99%